2011
DOI: 10.1143/apex.4.062701
|View full text |Cite
|
Sign up to set email alerts
|

Response Time-Shortened Zinc Oxide Scintillator for Accurate Single-Shot Synchronization of Extreme Ultraviolet Free-Electron Laser and Short-Pulse Laser

Abstract: We report an over one-order-of magnitude improvement in the response time of conventional hydrothermal method-grown zinc oxide (ZnO) scintillator by introducing additional quenching channels via intentional indium ion doping. A 3-ps fluorescence decay time constant is achieved, therefore making it the fastest scintillator operating below 100 nm to date. Using this indium-doped ZnO, relative jitter between extreme ultraviolet free electron laser (EUV-FEL) probe and optical pump pulses is evaluated to be less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Single crystals of PbWO 4 and Ce:YAG were grown from high-temperature melt of the corresponding material using the Czochralski technique [16,17] while monocrystalline ZnO was prepared by a conventional hydro-thermal technique [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single crystals of PbWO 4 and Ce:YAG were grown from high-temperature melt of the corresponding material using the Czochralski technique [16,17] while monocrystalline ZnO was prepared by a conventional hydro-thermal technique [7].…”
Section: Methodsmentioning
confidence: 99%
“…The scintillator properties required for short-wavelength laser beam characterization and imaging are as follows: a high yield of luminescence, a well-defined dependence of the yield on radiation properties (e.g., well-known dependence of the yield as a function of radiation intensity) fast response to the ultra-short laser pulses, sufficiently high absorption coefficient and damage threshold. For example, PbWO 4 [5,6] or ZnO [7] single crystals, with decay times of 2-3 ns and less than 1 ns (down to a few picoseconds dependent on doping concentration), respectively, can be used for detecting, timing and imaging short and ultra-short pulses of x-ray lasers [1][2][3][4]. The third material chosen for our experiment, Ce:YAG (Ce:Y 3 Al 5 O 12 ) crystal, is widely used for the soft X-ray laser beam imaging and characterization because of its high luminescent yield and excellent radiation resistance [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies done on the effect of impurity doping on ZnO have shown that there is a compromise between decay time and fluorescence intensity. Because of the fluorescence quenching effect of the Fe-impurities, the faster decay time comes with weaker fluorescence intensity [11]. 3d transition metals such as Fe in other semiconductor materials are known to play the role of lifetime-shortening impurity.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we have succeeded in shortening its emission lifetime to less than 100 ps and its rise time to 10 ps by intentional Fe ion-doping. Results have also revealed the dependence of fluorescence intensity and decay time on the type of dopant ion [18]- [21].…”
mentioning
confidence: 93%